Photos of Old Watkins Family Collage Photographs - Watkins, Howard::::::::: (1988)
Insert: 1945 Miriam Jean Watkins at Lake Park, Huntington Beach 1944 Esther Fine touching Rose Watkins pregnant with Miriam Jean Watkins; Marsha Fine hanging on jungle gym bar Esther is Rose's older half-sister